Analysis of Start-Up Share Valuation on the Indonesia Stock Exchange for the 2017-2022 Period Using the DFC GMV and Tobins'q Methods - Hartono Hartono (Newinera Publisher, 2022)
The phenomenon of the proliferation of startup companies in Indonesia that cannot be separated from the use of digital technology brings a fragrant aroma to venture capital investment companies. The number of startup companies that received the investment funds are bringing them to the Indonesian Stock Exchange by conducting an IPO even though the company has not been established for a long time. There is a correlation between the rapid growth of startups in Indonesia with